2011
DOI: 10.1111/j.1532-950x.2011.00877.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Transvaginal Natural Orifice Transluminal Endoscopic Surgery (NOTES®) and Laparoscopy for Elective Bilateral Ovariectomy in Standing Mares

Abstract: Bilateral ovariectomy by transvaginal NOTES or laparoscopy resulted in minimal inflammation and surgical trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
1
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 40 publications
3
39
1
5
Order By: Relevance
“…Fibrosis of the descending colon mesentery has also been observed 3 weeks after ovariectomy with the same vessel sealing and dividing device applied in the present report, although this instrument generates minimal collateral thermal spread and rapid tip cooling when compared with other devices . In another publication, blanching of the duodenal serosa was noted during ovariectomy, when the device was activated while its tip was in contact with the duodenum cranial to the ovarian pedicle for approximately 1 second . This contact resulted in serosal fibrosis 3 weeks postoperatively, but was not associated with clinical signs .…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Fibrosis of the descending colon mesentery has also been observed 3 weeks after ovariectomy with the same vessel sealing and dividing device applied in the present report, although this instrument generates minimal collateral thermal spread and rapid tip cooling when compared with other devices . In another publication, blanching of the duodenal serosa was noted during ovariectomy, when the device was activated while its tip was in contact with the duodenum cranial to the ovarian pedicle for approximately 1 second . This contact resulted in serosal fibrosis 3 weeks postoperatively, but was not associated with clinical signs .…”
Section: Discussionsupporting
confidence: 61%
“…The surgical times observed in this study were similar to those observed with previous laparoscopic ovariectomy techniques. The duration of bilateral laparoscopic ovariectomy performed through bilateral incisions range from 102 to 128 min (mean or median), when a vessel sealing device similar to ours was used . The mean surgical time of the left paralumbar ovariectomy was 76 minutes, gradually decreasing throughout the study.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…), whereas no correlation is found between serum amyloid A and pain (Pader et al . ). In horses with colic and other moderate to severe disease, HR, RR and blood pressure may well be affected by pain but may also be altered by endotoxaemia, cardiovascular compromise and/or dehydration.…”
Section: Physiological Parameters In Equine Pain Scalesmentioning
confidence: 99%
“…However, it is also possible that the inflammatory response was a response to air within the mediastinum. Air within body cavities, as occurs during laparoscopy, are known to cause an inflammatory response which can result in fever 12. There was also evidence of an inflammatory response in human cases of pneumomediastinum; 39 per cent of human patients with spontaneous pneumomediastinum had increased white blood cell counts 4…”
Section: Discussionmentioning
confidence: 99%